(untitled) (Bangladesh Journal of Plant Taxonomy, 2015)
The four sections of the little known genus Dimeria R. Br. of the rather anomalous paleotropical subtribe Dimeriinae Hack. (PoaceaePanicoideaeAndropogoneae) are revised. A key is provided. Three Peninsular Indian species, viz. Dimeria sivarajanii, D. idukkiensis and D. borii are treated here as subspecies of D. bialata, D. kurumthotticalana and D. mooneyi respectively; and five, viz. D. chelariensis, D. copei, D. eradii, D. jayachandranii and D. kollimalayana are reduced to synonymy. Bangladesh J. Plant Taxon. 22(1): 4754, 2015 (June)